Teaching of National Programme of Health Development to Undergraduates - S. Zuraida Zulkarnain (Paediatrica Indonesiana, 1974)
The practice of community medicine is the delivery of comprehensive health care by a health team trained in curative and preventive medicine to a defined population based on their needs and economy. For some time it has been realized that the integration of curative and preventive services is a well recognized national need. Only such a unification could effectively deliver comprehensive health care to the family which is the ultimate recipient of community care. The success in the application of the health care depends mainly on the training and attitude of the future doctors who are willing to work in the rural areas. It is therefore the responsibility of the medical school to train community oriented doctors, and such a training requires the provision of community projects in which students of the Medical School can participate.